Pengaruh Budaya Organisasi dan Motivasi terhadapn Kinerja Karyawan PT. Bank Kalsel Capem Pemprov Banjarbaru - Nurul Qomariyah Wulandari; Sulastini Sulastini; Jamaluddin Jamaluddin (Universitas Lambung Mangkurat, 2014)
This research aimed to determine the influence of organizational culture and motivation to increase employee performance. Organization needs employee in operate its operational activities. Because the employee is an important asset of an organization, so many things must be considered related to the increasing of job achievement. A good achievement is one of organization objective in obtain the higher job productivity. The achievement of the job performance did not separated from the quality of human resources quality. As wellnas another organization, PT Bank Kalsel need a qualified human resources in support and achieve ot organization objectives.The research have been conducted at PT. Bank Kalsel Capem Pemprov in Banjarbaru. This study was conducted by using a descriptive quantitative research. The sample was the employees at PT Bank Kalsel Capem Pemprov Banjarbaru and the amount are 12 persons. The data were obtained by doing interview, documentation study, and giving questionnaires to the sample. The variables were examined by using Likert Scale. Validity and Reliability test were used to test the questionnaires. Processing data in SPSS 21.0 version were analyzed by using descriptive analysis and the hypothesis was analyzed by using multiple linier regressions.The conclusion of this research is that: Partially, the organizational culture variables and motivation have positive and significant impact on employee performance, and that job organization culture dan motivation has a positive and significant influence to the employee performance of the PT Bank Kalsel Capem Pemprov Banjarbaru.Keywords: Organizational Culture, Motivation, Employee Performance